Nutrition Counseling and Stunting Care with Pregnant Women and Toddler Mothers in Temiyang Village, Kroya District, Indramayu Regency - Rizal Teguh Pratama; Dina Agustin; Hanifah Aenin (Kawakib: Journal of Multidisciplinary Research, 2025)
Stunting is a chronic nutritional problem resulting from a lack of nutritional intake over a long period of time, resulting in impaired growth in children or what is called a condition of failure to thrive in the womb until the baby is 2 years old. Clean and Healthy Living Behavior is one of the indirect factors that causes a person's nutritional and health status, especially for toddlers. Efforts to prevent and reduce stunting rates can be done by implementing a healthy and clean lifestyle and also getting used to eating foods with balanced nutrition. The aim of holding community service with the Real Work Lecture program with the theme of nutrition education and stunting care is so that people are more aware of the dangers of stunting, understand balanced nutrition and can help reduce stunting rates in the future. The method used is to provide outreach on nutrition and clean and healthy lifestyles targeting pregnant women and mothers of toddlers. From the results of observations in Temiyang Village, there are still many people who do not know how to process waste properly and lack self-awareness of the environment as well as mothers' lack of knowledge about managing balanced nutrition, especially in the First 1000 Days of Life.